18-β Glycyrrhetinic acid alleviates 2-acetylaminofluorene-induced hepatotoxicity in Wistar rats: Role in hyperproliferation, inflammation and oxidative stress. (June 2015) - Hasan, SK; Khan, R; Ali, N; Khan, AQ; Rehman, MU; Tahir, M; Lateef, A; Nafees, S; Mehdi, SJ; Rashid, S; Shahid, A; Sultana, S
2-Acetylaminofluorene (2-AAF) is a known hepatic carcinogen which leads to tumour formation in rodents. 18-β Glycyrrhetinic acid (18 β -GA) derived from liquorice plant has various pharmacological properties such as anti-ulcer, anti-inflammatory, antiviral, hepatoprotective and antioxidant. This study is designed to elucidate the chemopreventive properties of 18 β -GA against 2-AAF-induced liver toxicity in Wistar rats and evaluated its effect on inflammatory and tumour promotion marker and activities of different oxidative stress enzymes. Administration of 2-AAF at the dose of (50 mg/kg body weight (b.w.) intraperitoneally (i.p.)) for five consecutive days induces hepatic toxicity, inflammation, oxidative stress and hyperproliferation. Pretreatment with 18 β -GA at two different doses (45 and 75 mg kg −1 b.w.) significantly ameliorates 2-AAF-induced increased lipid peroxidation, alanine transaminase and aspartate transaminase, xanthine oxidase activities and activities of phase-II detoxifying enzymes along with the levels of glutathione content. Administration of 18 β -GA also significantly restored the expressions of proliferating cell nuclear antigen, cyclooxygenase 2, inducible nitric oxide synthase and nuclear factor κB. Furthermore, histological observations also support the preventive effects of 18 β -GA. Our findings suggest that pretreatment with 18 β -GA showed potential hepatoprotective effects via attenuation of oxidative stress, inflammation and hyperproliferation.